MODIFICATION OF HIERARCHICAL METHOD OF RBF FOR 3D-MODELS ON THE RESULTS OF LASER SCANNING - Babkov, V. S. (Radio Electronics, Computer Science, Control, 2008)
In article problem of surface build in 3D based on 3D laser scan data is reviewed. Modified method based on hierarchical RBF but adapted for 3D and has decrease time cost is described. Method efficiency is experimentally accepted.